Sleeping with the enemy: Science and the humanities still pass each other like ships in the night: Many complex policy problems will yield to the latest science, so policy wonks need more face time with science nerds, writes Roger Bradbury. - Bradbury, Roger (New Zealand Science Review, 2017)
​Many complex policy problems will yield to the latest science, so policy wonks need more face time with science nerds, writes Roger Bradbury. You’ve seen them all before, likely next to those ghastly management guru books in the airport bookshop. I’m talking aboutthe books that popularise the latest scientific breakthroughs and tell you how they will revolutionise your business. And if your business is policy-making, they promise to revolutionise that too.